Cultural Studies and Environmentalism
XXVIII, 496 p.
Keywords: As the first book to explore the confluence of three emerging yet critical fields of study, this work sets an exacting standard. The editors’ aim was to produce the most authoritative guide for ecojustice, place-based education, and indigenous knowledge in education. Aimed at a wide audience that includes, but is not restricted to, science educators and policymakers, Cultural Studies and Environmentalism starts from the premise that schooling is a small part of the larger educational domain in which we live and learn. Informed by this overarching notion, the book opens up ways in which home-grown talents, narratives, and knowledge can be developed, and eco-region awareness and global relationships can be facilitated. Incorporating a diversity of perspectives that include photography, poetry and visual art, the work provides a nuanced lens for evaluating educational problems and community conditions while protecting and conserving the most threatened and vulnerable narratives. Editors and contributors share the view that the impending loss of these narratives should be discussed much more widely than is currently the case, and that both teachers and children can take on some of the responsibility for their preservation. The relevance of ecojustice to this process is clear. Ecojustice philosophy is a way of learning about how we frame, or perceive, the world around us—and why that matters. Although it is not synonymous with social or environmental justice, the priorities of ecojustice span the globe in the same way. It incorporates a deep recognition of the appropriateness and significance of learning from place-based experiences and indigenous knowledge systems rather than depending on some urgent “ecological crises” to advocate for school and societal change. With a multiplicity of diverse voices coming together to explore its key themes, this book is an important starting point for educators in many arenas. It brings into better focus a vital role for theEarth’s ecosystems in the context of ecosociocultural theory and participatory democracy alike. “Encompassing theoretical, empirical, and experiential standpoints concerning place-based knowledge systems, this unique book argues for a transformation of (science) education’s intellectual tradition of thinking that emphasizes individual cognition. In its place, the book offers a wisdom tradition of thinking, living, and being that emphasizes community survival in harmony within itself and with Mother Earth.” Glen Aikenhead.